Block self-cross-linkable poly(ethylene terephthalate) copolyester via solid-state polymerization: Crystallization, cross-linking, and flame retardance. (23rd July 2015) - Zhao, Hai-Bo; Wang, Xiao-Lin; Guan, Yue; Wang, Xiu-Li; Chen, Li; Wang, Yu-Zhong
Abstract: A self-cross-linkable poly(ethylene terephthalate) block copolyester (SSP-PETPx) has been synthesized via solid-state polymerization (SSP). In the SSP process, a cross-linkable monomer named 4-(phenylethynyl) di(ethylene glycol) phthalate (PEPE) is incorporated into the amorphous phase of PET. The sequence distribution of the resulted copolyester SSP-PETPx is analyzed with 1 H NMR, showing that the SSP sample possesses block structure. Wide-Angle X-ray diffraction (WAXD) and differential scanning calorimetry (DSC) show that SSP-PETPx is crystallizable benefitting from its block structure, while the corresponding random copolyester (RD-PETP) is totally amorphous. The segments containing PEPE determine the extent of crystallization. Simultaneous thermogravimetric-differential scanning calorimetry (TG-DSC) and rheological analysis prove the cross-linking behaviour of SSP-PETP although the block constitution slightly postpones cross-linking occurrence. The high complex viscosity of the SSP-PETP at 340 °C suggests good flame retardancy and anti-dripping properties. Micro combustion calorimeter (MCC) results prove both SSP-PETP and RD-PETP copolyesters have low flammability, which demonstrates that block structure of SSP-PETP doesn't have a negative impact on the flammability of copolyesters. Graphical abstract: Highlights: A self-cross-linkable PET block copolyester was synthesized via SSP. Benefitting from block structure, the copolyester was crystallizable after SSP. The copolyester kept cross-linking activity and flame retardance simultaneously.